Treatment of whey wastewater by supercritical water oxidation - Sogut, Onur O.; Kipcak, Ekin; Akgun, Mesut (IWA PUBLISHING, 2011)
Whey wastewater is a by-product of cheese industry, which causes environmental pollution problems due to its containment of heavy organic pollutants. Conventional methods such as biological treatment and physico-chemical treatment are insufficient or ineffective. In this paper, the treatment of cheese whey wastewater has been carried out by supercritical water oxidation, using hydrogen peroxide as oxidant. The reaction conditions ranged between temperatures of 400-650 degrees C and residence times of 6-21 s under a pressure of 25 MPa. Treatment efficiencies based on TOC removal were obtained between 75.0% and 99.81%. An overall reaction rate model, which consists of the hydrothermal and the oxidation reactions, was determined for the hydrothermal decomposition of the wastewater with an activation energy of 50.022 (+/- 1.7) kJmol(-1) and a pre-exponential factor of 107.72 (+/- 4.1) s(-1). The oxidation reaction rate orders for the TOC and the oxidant were 1.2 (+/- 0.4) and 0.4 (+/- 0.1) respectively, with an activation energy of 20.337 (+/- 0.9) kJmol(-1), and a pre-exponential factor of 1.86 (+/- 0.5) mmol(-0.6)L(0.6)s(-1) in a 95% confidence level.
Keywords: cheese whey wastewater; oxidation; reaction kinetics; supercritical water; treatment; CHEESE WHEY; BATCH; DECOMPOSITION; REMOVAL; REACTOR; Engineering; Environmental Sciences & Ecology; Water Resources